The effect of topography on water wetting and micro/nano tribological characteristics of polymeric surfaces - Yoon, ES; Yang, SH; Kong, H; Kim, KH (KLUWER ACADEMIC/PLENUM PUBL, 2003)
The effect of surface topography on the water-wetting nature and micro/nano tribological characteristics of polymer surfaces was experimentally studied. A plasma-treated thin polymer film and ion-beam-treated PTFE (polytetrafluoroethylene) were used as. at specimens. Thin polymer films were deposited on Si-wafer (100) by the parallel-plate plasma technique. The ion-beam-roughening treatment was performed to change the PTFE surface topography using a hollow cathode ion gun under different argon-ion dose conditions in a vacuum chamber. Micro and nano tribological characteristics, water-wetting angles and roughness were measured with a micro-tribotester, SPM (scanning probe microscope), contact anglemeter and profilometer, respectively. The plasma-treated thin polymer film and ion-beam-treated PTFE surfaces were rendered increasingly hydrophobic as a function of the treatment time. The wetting characteristics were strongly dependent on the micro-roughness and the sharpness of the asperities. The tribological characteristics on the nano-scale showed different results from those on the micro-scale. It was noted that the contact-size ratio, especially the ratio of the tip or ball to the average surface roughness at a standard cut-off length, should be considered for evaluating the micro- and nano-scale tribological test results.